A framework for advancing sustainable magnetic resonance imaging access in Africa. (16th November 2022) - Anazodo, Udunna C.; Ng, Jinggang J.; Ehiogu, Boaz; Obungoloch, Johnes; Fatade, Abiodun; Mutsaerts, Henk J. M. M.; Secca, Mario Forjaz; Diop, Mamadou; Opadele, Abayomi; Alexander, Daniel C.; Dada, Michael O.; Ogbole, Godwin; et al.
Abstract: Magnetic resonance imaging (MRI) technology has profoundly transformed current healthcare systems globally, owing to advances in hardware and software research innovations. Despite these advances, MRI remains largely inaccessible to clinicians, patients, and researchers in low‐resource areas, such as Africa. The rapidly growing burden of noncommunicable diseases in Africa underscores the importance of improving access to MRI equipment as well as training and research opportunities on the continent. The Consortium for Advancement of MRI Education and Research in Africa (CAMERA) is a network of African biomedical imaging experts and global partners, implementing novel strategies to advance MRI access and research in Africa. Upon its inception in 2019, CAMERA sets out to identify challenges to MRI usage and provide a framework for addressing MRI needs in the region. To this end, CAMERA conducted a needs assessment survey (NAS) and a series of symposia at international MRI society meetings over a 2‐year period. The 68‐question NAS was distributed to MRI users in Africa and was completed by 157 clinicians and scientists from across Sub‐Saharan Africa (SSA). On average, the number of MRI scanners per million people remained at less than one, of which 39% were obsolete low‐field systems but still in use to meet daily clinical needs. The feasibility of coupling stable energy supplies from various sources has contributed to the growing number of higher‐field (1.5 T) MRI scanners in the region. However, these systems are underutilized, with only 8% of facilities reporting clinical scans of 15 or more patients per day, per scanner. The most frequently reported MRI scans were neurological and musculoskeletal. The CAMERA NAS combined with the World Health Organization and International Atomic Energy Agency data provides the most up‐to‐date data on MRI density in Africa and offers a unique insight into Africa's MRI needs. Reported gaps in training, maintenance, and research capacity indicate ongoing challenges in providing sustainable high‐value MRI access in SSA. Findings from the NAS and focused discussions at international MRI society meetings provided the basis for the framework presented here for advancing MRI capacity in SSA. While these findings pertain to SSA, the framework provides a model for advancing imaging needs in other low‐resource settings. Abstract : Africa has a massive population with few infrastructural resources and an untapped potential to effect transformative change in healthcare. To advance magnetic resonance imaging (MRI) access across all African countries and improve health and well‐being in low‐resource settings over the next decade, the MRI community is called to partner with the Consortium for Advancement of MRI Education and Research in Africa (CAMERA) to create enabling clinical and research MRI environments that will utilize the rich intellectual resources in Africa to realize lasting and equitable MRI for all Africans and the world at large.